Pengaruh Proses Perlakuan Panas terhadap Nilai Kekerasan Metal Matrix Composite Coating pada Substrat SS316 untuk Aplikasi Pipa Boiler [The Effect of Heat Treatment Process on Hardness Value of Metal Matrix Composite Coating on SS316 Substrate for Boiler] - Martides, Erie (Jurnal Metalurgi, 2018)
Deposition of MMC (metal matrix composite) Coating of NiCr+Cr3C2+Al2O3 and NiCr+WC12Co+Al2O3 on the surface of SS316 material for coal fire boiler application have been performed using HVOF (high velocity oxygen fuel) technique with constant parameters of fuel pressure and spray distance After that the MMC layers are heated with temperature variation of 600, 700 and 800 °C with water quenched to obtain optimum hardness value according to the application of boiler tube of power plant. The highest hardness value applied to the NiCr+WC12Co+Al2O3 layer with the heat treatment process of 800 °C ie. 551.31 VHN